Current condition of the systems of agricultural production in the region, in terms of innovation based on ISO norm 9001. - Manjarres Chica, Virginia; Martínez Mantilla, Daniel; Toledo Cortés, Natalia (SATHIRI, 2020)
In the book “agricultural production and development system”. Philippe Colin (1993). Mexico. “A production system can be considered as the result of ecosystems, forms of socio-economic organization and practicable techniques. The objectives of production, the way humans make their decisions, the criteria they optimize, the rationalities of their behavior depend fundamentally on the structure of the basic socio-economic units, components of  conomic and social formations “. This research was intended to understand the current studies of agricultural production systems in the city-region, in terms of innovation with standards based on ISO 9001. It was possible to identify what productive vocations in the rural area of the city, where instruments were applied to around 130 peasant of the zone, who are the people who have variety of crops and are exporting to countries like, Venezuela, Australia, Canada and Brazil. The methodology used was mixed (qualitative and quantitative) that allowed to be based on the description of how the agricultural production systems are being carried out in Cundinamarca and the region. Based on knowledge that should be applied in the spaces of production systems, strengthening innovation, which allowed a management of the solutions, with a more responsible and participative attitude,where it was clearly defined the learning of new techniques of food, innovative of productive systems and practices supported by clean and technified products management can be the support of innovation, structuring a sector based it´s information.
Keywords: Production Systems; Producers; Productive vocations; Agriculture; Crops